Estimating Inclusiveness of Growth in Sub-Sahara African Countries: a VAR Approach - Kehinde Kabir Agbatogun; Sunday Idowu Oladeji; Adewale Abiodun Adegboye (Jurnal Ekonomi dan Studi Pembangunan, 2022)
The study examined the interaction among income inequality, economic growth, and poverty with a view of assessing the extent of inclusiveness of growth in selected African countries. Using a dataset from World Development Indicators (WDI) and Standardized World Income Inequality Dataset (SWIID), the study adopted Vector AutoRegression (VAR) method in its econometric analysis. Its findings show that only "West" African countries exhibit partial traits of inclusiveness of growth. Thus, the study recommends the provision and implementation of distributional and growth-oriented macroeconomic policies, as well as investment in public infrastructure to spread the benefits of growth to all in African countries.